Features of Morphogenesis of Aortic Aneurysms on the Background of Hypertension and Associated Risk Factors - V. Zakharova; O. Rudenko; V. Kravchenko (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To investigate the role of hypertension and associated risk factors in the formation of aortic aneurysms.Material and methods. Retrospective analysis of 196 case histories of patients who were successively operated on for ascending aortic aneurysm at the National Amosov Institute of cardiovascular surgery. The history was analyzed, the duration and degree of hypertension were recorded, as well as other factors that may have influenced the development of ascending aortic aneurysm in some way. A pathomorphological examination of fragments of the aortic wall that were excised during the operation was performed.Out of all 294 examined patients operated for ascending aortic aneurysm, hypertension was reported in 196 (66.7%) patients. The incidence of ascending aortic aneurysm positively correlated with the duration of hypertension. The ma-jority of patients (118 [60.2%]) had signs of hypertension for more than five years. Additional ethiopathogenetic fac-tors were identified in patients with ascending aortic aneurysm and hypertension, with atherosclerosis ranking first (66 [33.6%]). The next factors that demonstrated the same incidence were the inflammatory process in the aorta and AV, and smoking: 45 cases each (22.9%). Then, in descending order, were: xenobiotics exposure (43 [21.9%]), rheumatic stenosis of AV (40 [20.4%]), chest injury (33 [16.8%]), dysplasia of AV (28 [14.3%]), alcohol abuse (13 [6.6%]), Marfan syndrome (9 [4.6%]), other (8 [4.1%]).The results of comparison of the history and pathomorphological findings allowed to develop a scheme of ascending aortic aneurysm pathogenesis in hypertension. The scheme of ascending aortic aneurysm pathogenesis in hypertension is discussed in the work. The results of morphological examination show that hypertension is associated with the dam-age to the aortic endothelium, which leads to fibromuscular proliferation of the intima with subsequent hypoxic damage to the inner layer of the media. Hypoxic damage to the media, which is associated with vasa vasorum remodeling due to hypertension, is also observed in the subventricular layer. Weakening of the aortic wall at elevated pressure causes dila-tation of the aorta, i.e. the formation of an aortic aneurysm. This process may be exacerbated by additional factors, with atherosclerosis being the most common (33.6%)